The Palace and Botanical Garden in Balchik – a possible nomination for cultural landscape of the UNESCO list (Research Announcements "Heritage BG", 2025)
The research is a proposal for the UNESCO list of the Palace and Botanical Garden of Balchik as a cultural landscape. It is structured following the Operational Guidelines for the Implementation of the World Heritage Convention. The research could serve as a proposal for a cultural landscape for Bulgaria, as the country does not have a single one of this type on the World Heritage List.
Keywords: World Heritage Sites; nominated property; Queen Maria; criteria; outstanding universal value; integrity; authenticity